Innovative Karawitan Artwork Ngulat | Karya Karawitan Inovatif Ngulat - I Made Agus Sumantra; I Ketut Partha (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
Coconut trees play an important role in people's lives in Bali. Coconut trees are very useful for Hindu religious ceremonies in Bali. Starting from coconut tree trunks can be used as material for building houses, coconut fruit can be used as a part of ceremonies and traditional medicine, coconut processed products can be used as coconut oil, and coconut leaves can be used as an offering of Hindu religious ceremonies in Bali. Based on this reality, the composer was inspired to use the coconut leaves as an idea to create a karawitan artwork entitled ''NGULAT''. Ngulat is a wickerwork or woven made of bamboo, pandan, or coconut leaves. The method used in the innovative karawitan artwork